2013
DOI: 10.1177/0148607113489151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymeric Formula vs Elemental Formula in Neonatal Piglets With Short Bowel Syndrome

Abstract: An overall benefit of the polymeric formula over the elemental formula on gut adaptation was not observed. Furthermore, SBS piglets without ileum had less ability to tolerate polymeric formula, contributing to more days of PN support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Studies in piglets that compared elemental diets with bovine milk-based diets have also uncovered potential benefits of elemental diets. Piglets are the best nonprimate model for studying neonatal nutrition because the gastrointestinal anatomy, physiology, and nutrient requirements of pigs are the most similar to humans (86). In one such study, Connor et al (87) compared polymeric and elemental formulas for 3 surgically created short-bowel syndrome groups: 1) midintestinal resection with a jejunoileal anastomosis (equal amount of jejunum and ileum remaining) (n = 16); 2) distal intestinal resection, including the ileum, cecum, and 5 cm of the spiral colon, with a jejunocolic anastomosis (n = 17); and 3) sham surgery (n = 15).…”
Section: Sources Of Nutritionmentioning
confidence: 99%
“…Studies in piglets that compared elemental diets with bovine milk-based diets have also uncovered potential benefits of elemental diets. Piglets are the best nonprimate model for studying neonatal nutrition because the gastrointestinal anatomy, physiology, and nutrient requirements of pigs are the most similar to humans (86). In one such study, Connor et al (87) compared polymeric and elemental formulas for 3 surgically created short-bowel syndrome groups: 1) midintestinal resection with a jejunoileal anastomosis (equal amount of jejunum and ileum remaining) (n = 16); 2) distal intestinal resection, including the ileum, cecum, and 5 cm of the spiral colon, with a jejunocolic anastomosis (n = 17); and 3) sham surgery (n = 15).…”
Section: Sources Of Nutritionmentioning
confidence: 99%
“…Compared with intact protein, an elemental diet obviously requires less processing of protein digestion before absorption. And also report of Hua et al showed that SBS piglets without ileum had less ability to tolerate polymeric formula [11]. Interestingly, the patient was given a polymeric formula with fiber first.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, the patient was recommended a polymeric high caloric formula through ileostomy which resulted in his readmission with relapse of acute renal failure and decline in nutritional status. Inclusion of polymeric formula instead of elemental formula in postoperative diet for jejunocolic anastomosis has been linked to negative clinical outcomes including diarrhea and longer duration of parental support [12].…”
Section: Discussionmentioning
confidence: 99%